Richness, endemism and conservation of sigmodontine rodents in argentina - Formoso, Anahí Elizabeth (2019)
Sigmodontine rodents, with 86 genera and ~430 living species, constitute one of the most successful radiations of Neotropical mammals. In this contribution, we studied the distributional ranges of 108 sigmodontine species in Argentina. Our objectives were (i) to establish geographical patterns of species richness and endemism, and (ii) to evaluate the regional conservation status of these taxa. We constructed a minimum convex polygon for each species, using information from literature and biological collections. Individual maps were superimposed on a map of Argentina divided into cells of 25 km on each side. For each cell, we calculated the species richness, which varied between 1 and 21 species, and its degree of endemism, which fluctuated between 0.001 and 3.28. There were 30 species of sigmodontine rodents distributed almost exclusively in Argentina, most of them restricted to forested areas (Southern Andean Yungas) or to arid and semiarid environments (High and Low Monte and Patagonian Steppe). Areas with high species richness and endemism scores corresponded grossly with the Southern Andean Yungas, the Humid Chaco plus the Paraná flooded savannas, the Alto Parana Atlantic forests plus the Araucaria moist forests, the High Monte and the ecotone between the Patagonian steppe and the Valdivian temperate forests. A reassessment of the conservation status of sigmodontine rodents distributed in Argentina retrieved 2 extinct species, 7 endangered, 7 vulnerable, 6 near threatened and 13 data deficient. These numbers suggest a much more serious situation than the expressed by previous evaluations, highlighting the urgent need to establish conservation measures for the protection of this group.